Foundations for a core ontology of manufacturing - Borgo, Stefano (2010)
An initial fragment of a core ontology for the manufacturing domain is presented and motivated. It consists of an ontological classification of ADACOR concepts according to the DOLCE foundational ontology. The ontology is conceptually transparent and semantically explicit thus suitable for information communication, sharing, and retrieval. The system here described considers entities performing the manufacturing scheduling and control operations only.